Priorities for Sustainable Growth : A Strategy for Agriculture Sector Development in Tajikistan - World Bank (Washington, DC, 2013)
Agriculture sector growth has made a powerful contribution to post-war economic recovery in Tajikistan, accounting for approximately one third of overall economic growth from 1998 to 2004. Sector output increased by 65 percent in real terms during this period, and has now returned to the level extant at independence in 1990. Total Factor Productivity (TFP) has also increased, by 3 percent per year. Despite this progress, there is legitimate concern that this growth is unsustainable. Evidence suggests that it has been driven largely by the external factors noted above, rather than substantive changes to resources, incentives and the behavior of factor and commodity markets. First, an extensive program of policy reform, particularly in the area of land ownership, has yet to make a substantial impact on the incentive structure for agricultural workers cultivating the majority of arable land. Second, sustainable growth requires positive net investment. Third, commodity markets remain weak, with a limited capacity to translate increased demand into improved production incentives. And fourth, growth in crop production has been largely driven by low value food and cereal crops. A sustainable increase in access to rural finance will require much greater emphasis on the development of alternative sources of finance for all of agriculture, in addition to resolution of the cotton debt crisis. The capacity for agricultural loan appraisal and management also needs to be strengthened, new collateral instruments introduced and new loan products developed, which are suited to agriculture in general and small-scale farmers in particular.